On the aggregate effects of immigration in Spain - Mario Izquierdo; Juan F. Jimeno; Juan A. Rojas (SERIEs - Journal of the Spanish Economic Association, 2010)
Over the period 19952006 the Spanish economy experienced a rapid increase in employment and output growth, a surge in investment over GDP, a substantial deterioration in the current account balance and an improvement in the finances of the social security system. This paper presents a dynamic general equilibrium model designed to quantify the role played by immigration in shaping these facts. In the context of the aging of the Spanish population, we also analyze the medium and long run effects of the immigration process accounting for relevant supply and demand effects. This is done by allowing for enough heterogeneity in the demographic characteristics of immigrant and native workers in a way that allow us to perform counterfactual experiments regarding the flow of immigrants and its skill composition.
Keywords: E20; J10; 330; overlapping generations; immigration; Einwanderung; Makroökonomischer Einfluss; Dynamisches Gleichgewicht; Spanien